2017
DOI: 10.6090/jarq.51.165
|View full text |Cite
|
Sign up to set email alerts
|

Change in Lymphocyte Subsets of Holstein Calves Caused by Short-term Transportation

Abstract: In order to study the possibility of using lymphocyte subsets as a stress indicator, the changes of the subset proportion in peripheral blood were examined after transportation. Six 3-month-old male Holstein calves were transported for about 3 h in a lorry via an ordinary road. Blood samples were collected at the expected unloading time on the day before transport (T0), immediately after unloading (T1), 24 h after unloading (T2), and 1 week after unloading (T3). CD2, CD4, CD8, CD21, CD25, WC1, and NKp46 antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To our knowledge, there are limited and contrasting results on which part of the immune system of young calves is affected by transport. Following transport, for example, percentages of γδ T cells, that represent up to 60% of circulating T-cells in young calves, have been reported to increase [ 8 , 9 ]. However, Riondato et al [ 10 ] showed a decrease in percentages of these cell populations, whereas Baldwin et al [ 11 ] reported a significant fluctuation in their proportion.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are limited and contrasting results on which part of the immune system of young calves is affected by transport. Following transport, for example, percentages of γδ T cells, that represent up to 60% of circulating T-cells in young calves, have been reported to increase [ 8 , 9 ]. However, Riondato et al [ 10 ] showed a decrease in percentages of these cell populations, whereas Baldwin et al [ 11 ] reported a significant fluctuation in their proportion.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are limited and contrasting results on which part of the immune system of young calves is affected by transport. Following transport, for example, percentages of γδ T cells, that represent up to 60% of circulating T-cells in young calves, have been reported to increase(Anane et al, 2010;Kanematsu et al, 2017). However,Riondato et al (2008) showed a decrease in percentages of these cell populations, whereasBaldwin et al (2000) reported a significant fluctuation in their proportion.…”
mentioning
confidence: 99%